Perencanaan dan Pengembangan SDM Dalam Mendorong Percepatan Pembangunan Ekonomi - ., Arismunandar (Program Studi Administrsi Pendidikan Program Pascasarjana UNM, 2013)
Indonesian economic development vision in 2025 is to create a Indonesian society which are independent, progressive, fair and prosperous. To achieve that mission, the government compile a master plan acceleration and expansion of Indonesias economic development ( MP3EI) which include the increasing of adding value and expanding the value chain of production and distribution processes of asset management and access (potential) natural resources, geographic regions and human resources, through creation of an integrated economic activity and synergy within and between regional centers of economic growth. The concept of a regions economic growth become keyword of MP3EI has implications for human resources to support the process of innovation and providing skilled manpower. Based on approach to labor planning needs, it can be formulated in the number, type and qualification of human resources necessary for the economic development of Indonesia.